Immobilization of a Pleurotus ostreatus Laccase Mixture on Perlite and Its Application to Dye Decolourisation - Pezzella, Cinzia (Hindawi Publishing Corporation, 2014)
In the present study, a crude laccase preparation from Pleurotus ostreatus was successfully immobilized on perlite, a cheap porous silica material, and tested for Remazol Brilliant Blue R (RBBR) decolourisation in a fluidized bed recycle reactor. Results showed that RBBR decolourisation is mainly due to enzyme action despite the occurrence of dye adsorption-related enzyme inhibition. Fine tuning of immobilization conditions allowed balancing the immobilization yield and the resulting rate of decolourisation, with the adsorption capacity of the solid biocatalyst. In the continuous lab scale reactor, a maximum conversion degree of 56.1% was achieved at reactor space-time of 4.2 h. Stability and catalytic parameters of the immobilized laccases were also assessed in comparison with the soluble counterparts, revealing an increase in stability, despite a reduction of the catalytic performances. Both effects are most likely ascribable to the occurrence of multipoint attachment phenomena.